Dampak Faktor Sosial Ekonomi Petani Terhadap Produksi Usahatani Padi Di Desa Jatisela Kecamatan Gunungsari Kabupaten Lombok Barat - Ahmad Suriadi; Muhammad Hamsyuni (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2026)
This study aims to analyze the effect of farmers’ socioeconomic factors on rice farming production in Jatisela Village, Gunungsari District, West Lombok Regency. The variables examined include age, education level, farming experience, the role of extension services, farmer organizations, number of household dependents, farm size, labor, and capital. This research uses a quantitative approach with multiple linear regression analysis involving 65 farmer respondents selected through simple random sampling. Data were collected through interviews, observation, and documentation, and analyzed using the coefficient of determination (R²), F-test, and t-test. The results show that the model has an R² value of 0.593, indicating that 59.3% of the variation in rice production is explained by the independent variables in the model. Simultaneously, all socioeconomic variables significantly influence rice production. However, partially, only farm size has a positive and significant effect on rice production, while other variables do not show a statistically significant influence. These findings indicate that land size remains the dominant factor determining rice production in Jatisela Village, whereas other socioeconomic factors have not yet contributed optimally to production improvement. Therefore, strengthening institutional capacity, agricultural technology adoption, and farm management systems is required to achieve sustainable productivity improvement.